PENGARUH DEVIASI DAN KETERLAMBATAN UPDATE ECDIS TERHADAP KESELAMATAN PELAYARAN KAPAL MV. ALIYAH PRATAMA - Brainando Satrio; B.L. Hentri Widodo; Nor Sa'adah; Retno Indriyati (UNIMAR AMNI Semarang, 2026)
This study aims to explain and describe the influence of shipping deviation in supporting shipping safety. Explaining the impact of delays in ECDIS updates on supporting shipping safety. Explaining and describing deviations and delays in ECDIS updates have the potential to increase risks to shipping safety on the MV. Aliyah Pratama. Through a quantitative approach, data were collected from questionnaires distributed to the crew of the MV. Aliyah Pratama, as well as direct observations in the field. The results of this study indicate that, the greater the influence of deviation, the greater the impact on shipping safety. Delays in ECDIS updates on ships will increase risks to shipping safety. The influence of deviations and delays in ECDIS updates has a very significant role in shipping safety. These findings emphasize that proper deviation management and regular ECDIS updates will support the creation of optimal shipping safety. Keywords: Deviation, ECDIS, Cruise safety.